Quando o silêncio é rompido: homossexualidades e esportes na internet - Luiza Aguiar dos Anjos (2013)
Homosexualities can be pointed out as a polemic topic that, as such, look overly unpleasent to be dealt with in daily journalism. Therefore, matters discussing them seem to gain notoriety only when episodes that break the routine occur, attracting society´s attention. What I call "episode Michael" was a recent example of that: in a match played for the semi-final of the Superliga masculina de vôlei (a national men's volleyball championship) between Sada Cruzeiro and Vôlei Futuro, an almost unison chorus of Cruzeiro´s fans screamed homophobic chanting against the player Michael, of the opposing team. At the end of the game, the player exposed his outrage over the incident and, thereafter, for weeks the situation was commented on media vehicles. The episode thus broke with the current silent about homosexuality, especially considering the sporting scenery. Therefore, the corpus of this research are the discourses published about the case on the sites of the newspapers Estado de Minas, Folha de São Paulo, O Estado de São Paulo and O Globo, through their articles and their respective comments from readers. These texts were analyzed from the perspective of a discourse approach, in which the analyzed contents are seen as discourses, built within networks of power, where certain representations assume a value of truth (Hall, 1997). The aim of this paper is to analyze these discourses, enabling reflections on homosexualities in sports and, more broadly, in society. I reflected on the virtual environment using the concepts of cyberculture (Lemos, 2004), network society (Castells, 2005), mediation (Martin-Barbero, 2003) and virtual community (Levy, 1999). I also discussed possible effects of anonymity in this space, based on the reflections of Marques (2006). Freedom of speech and censorship are concepts used by readers-commentators, most of which showed unawareness about the boundaries between the two categories. I treated the homosexualities from the perspectives of Gender Studies and Queer Theory. The speeches found, even among those who criticize the protests of the fans, are guided by heteronormative parameters, assuming an alignment between sex, gender and sexuality. Analyzing the specificity imposed by the sports scene, there is a strong presence of the symbolic violence. In this sense, discourses establish a battle: on one side, the defense for less aggressive behavior of fans in sports arenas; on the other, the legitimacy of the easing of standards of civility and violence. It is also found the possibility of an intermediate position that recognizes sporting arenas as a ritual space, but in which certain attitudes also require control. The arguments exposed are mostly guided by stereotypes of the sport and the fans that, regulated by networks of power, are taken as established truths, notions that I challenge.